Development and monitoring of an integrated bioprocess for production of a potential malaria vaccine with Pichia pastoris. (November 2015) - Borchert, Sven-Oliver; Voss, Tobias; Schuetzmeier, Fabian; Paul, Jessica; Cornelissen, Gesine; Luttmann, Reiner
Highlights: Pichia pastoris was used for expression of a potential malaria vaccine. An integrated bioprocess with expanded bed adsorption was set up. Design of experiments was applied successfully for process optimization. A golden batch model for monitoring of the integrated process was constructed. Abstract: An engineered variant of the yeast Pichia pastoris was used to produce the potential malaria vaccine D1M1. This paper describes the implementation of an expanded bed adsorption chromatography step into a sequential cultivation process of the yeast in order to link protein expression, cell release, and product capture of the secreted protein in a fully automated plant. The process is operated with a semi-continuous strategy for an integrated production. Process improvements have been achieved using design of experiments. Resulting purities of product achieved up to 87% with recoveries of 51% in a single downstream operation. Furthermore, a multivariate analysis of historical batch data was used to develop a golden batch model for process monitoring.